2016
DOI: 10.3928/01477447-20151228-03
|View full text |Cite
|
Sign up to set email alerts
|

Core Concepts: Orthopedic Intern Curriculum Boot Camp

Abstract: Orthopedic surgical interns must gain a broad array of clinical skills in a short time. However, recent changes in health care have limited resident-patient exposures. With the reported success of simulation training in the surgical literature, the American Board of Orthopaedic Surgery (ABOS) and Residency Review Committee for Orthopaedic Surgery have required that surgical simulation training be a component of the intern curricula in orthopedic surgical residencies. This study examined the short-term effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…In 2015, a study by Jones et al compared scores in task-specific measures between PGY-1 residents following a three-month orthopaedic "intern boot camp" and PGY-2 residents immediately following their orthopaedic internship that did not include the surgical skills curriculum. 7 The authors found that there was no difference in performance during the surgical skill examinations between the two groups.…”
Section: Discussionmentioning
confidence: 93%
“…In 2015, a study by Jones et al compared scores in task-specific measures between PGY-1 residents following a three-month orthopaedic "intern boot camp" and PGY-2 residents immediately following their orthopaedic internship that did not include the surgical skills curriculum. 7 The authors found that there was no difference in performance during the surgical skill examinations between the two groups.…”
Section: Discussionmentioning
confidence: 93%
“…With respect to the acquisition of orthopaedic skills, many studies have demonstrated that simulation results in improved clinical outcomes with proportional reduction in operating times, however not without substantial cost [39] . Previous literature has demonstrated that non-suite simulation offers an ideal platform in order to teach new orthopaedic interns the basic skills of splinting, casting, suturing and knot tying [40] . Furthermore, Seeley et al proposed that mobile life-sized prosthetic limbs are be suitable teaching adjuncts for practicing and mastering the skills of fracture reduction and immobilization [41] , whilst further studies have demonstrated standard-driven cast removal simulation training to aid trainee learning and ensure patient safety [ 42 , 43 ].…”
Section: Distance Learning With Specific Respect To Orthopaedic Surgical Trainingmentioning
confidence: 99%
“…Reports of graduate medical education curricula are limited to a few intern boot camps in surgical residencies, obstetrics and gynecology, pediatrics, and pediatric cardiology fellowships, [7][8][9][10][11][12][13] as well as reports of a simulation-based boot camp, ambulatory boot camp, and orientation workshops focused on safe handoffs and Accreditation Council for Graduate Medical Education General Competencies for internal medicine interns. [14][15][16][17] This curriculum is unique in that, to our knowledge, there are no published reports of a clinical reasoning-oriented, inpatientfocused transition curricula designed for newly deployed internal medicine interns, including in MedEdPORTAL.…”
Section: Citationmentioning
confidence: 99%